PENGARUH MOTIVASI DAN ETIKA KERJA ISLAM TERHADAP KOMITMEN ORGANISASI DI KOPERASI KARYAWAN PURA GROUP KUDUS - Limanihtada, Fathiyyatul; Suhadi, Suhadi (BISNIS, 2018)
This study aims to determine the effect of work motivation and Islamic work ethics on organizational commitment in the Pura Group Kudus Employee Cooperative. This type of research is field research, with a quantitative research approach. The number of research samples was 30 respondents. Primary data was obtained from questionnaires / questionnaires and processed using SPSS. The results showed that work motivation had a significant effect on organizational commitment, as evidenced by the value of t arithmetic (1.720> 1.703) and ρ value of 0.097. Whereas Islamic work ethic influences but is not significant to organizational commitment, evidenced by the value of t arithmetic (2.260> 1.703) and ρ value of 0.032.